Special Economic Zone at the Crossroads: The Case of Batam - Adiwan F. Aritenang (Jurnal Ilmu Sosial dan Ilmu Politik, 2017)
The establishment and development of Batam are very much related to Indonesia’s development itself. Considering its strategic location, since the 1970s, the Indonesian government has planned and developed Batam to catch economy spillovers from Singapore. The decentralization induces new development paths through critical juncture restructure the institutional setting in the Batam government and innovation of ICT by the Batam Indonesia Free Zone Authority (BIFZA leaders. These new paths introduce new development trajectories for Batam that has relied on manufacturing and infrastructure for its economic development. The paper analyses the impact of the political economy shift on Batam’s economic growth. Using historical institutionalism, the paper argues that the city exhibit urban economy resilience as, despite national politico-economy turbulence, the city creates new opportunities for alternative economic growth channels. The innovation, knowledge accumulation and strong informal ties allow the ICT sector to emerge as the driver of economic growth, adding to the manufacturing sector. This shows the importance of technology adaptation to avoid institutional lock-in and path dependence for local development.